Recurrence risk stratification and treatment strategies of patients with stage IVa‐b hypopharyngeal squamous cell carcinoma. Issue 9 (1st August 2022) - Heng, Yu; Xu, Chengzhi; Lin, Hanqing; Zhu, Xiaoke; Zhou, Liang; Zhang, Ming; Li, Ji; Tao, Lei
Abstract: Background: Optimal treatment strategies for patients with stage IVa‐b hypopharyngeal squamous cell carcinoma (HSCC) remain controversial. This study aimed to examine the high‐risk factors of postoperative tumor recurrence after surgical resection of HSCC and devise individualized postoperative adjuvant treatment (POAT). Methods: Overall, 218 patients with stage IVa‐b HSCC who received surgery as initial treatment and with negative surgical margins were evaluated. Independent risk factors of recurrence were identified, and survival outcomes were compared according to recurrence risk and POAT use. Results: POAT significantly improved recurrence‐free survival (RFS) and overall survival (OS) only in the high‐risk patients ( p = 0.003 and 0.018, respectively). Compared with postoperative radiotherapy alone, postoperative chemoradiotherapy (pCRT) achieved significantly better RFS ( p = 0.035) and OS ( p = 0.048). Conclusions: POATs are recommended for high‐risk patients with stage Iva‐b HSCC, with pCRT achieving superior outcomes. Regular re‐examination after tumor resection is sufficient for low‐risk patients.